BET inhibitors RVX-208 and PFI-1 reactivate HIV-1 from latency. Issue 1 (December 2017) - Lu, Panpan; Shen, Yinzhong; Yang, He; Wang, Yanan; Jiang, Zhengtao; Yang, Xinyi; Zhong, Yangcheng; Pan, Hanyu; Xu, Jianqing; Lu, Hongzhou; Zhu, Huanzhang
Abstract Persistent latent reservoir in resting CD4+ T cells is a major obstacle in curing HIV-1 infection. Effective strategies for eradication of the HIV-1 reservoir are urgently needed. We report here for the first time that two BET inhibitors, RVX-208, which has entered phase II clinical trials for diverse cardiovascular disorders, and PFI-1, which has been widely studied in oncology, can reactivate HIV-1 from latency. RVX-208 and PFI-1 treatment alone or in combination with other latency reversing agents efficiently reactivated HIV-1 transcription through an up-regulation of P-TEFb by increasing CDK9 Thr-186 phosphorylation in latently infected Jurkat T cellsin vitro . The two BET inhibitors also reactivated HIV-1 transcription in cART treated patient-derived resting CD4+ T cellsex vivo, without influence on global immune cell activation. Our findings, in combination with previous reports, further confirm that BET inhibitors are a group of leading compounds for combating HIV-1 latency for viral eradication.